A sustainable alkaline membrane fuel cell (SAMFC) stack characterization, model validation and optimal operation. (19th February 2020) - Raimundo, R.C.; Vargas, J.V.C.; Ordonez, J.C.; Balmant, W.; Polla, P.T.B.; Mariano, A.B.; Marino, C.E.B.
Abstract: This work introduces a sustainable alkaline membrane fuel cell, SAMFC, stack. The SAMFC includes a reactor that uses recycled aluminum to break the water molecule via the oxidation of aluminum catalyzed by NaOH in order to generate hydrogen to feed system. A cellulosic membrane supports the liquid electrolyte. CO2 purified air is obtained from atmospheric air that is filtered by a KOH solution, so that potassium carbonate is not formed. The prototype consisted of a four single alkaline membrane fuel cells, AMFC, the H2 -producing reactor, and the CO2 purifier. The SAMFC performance is evaluated via direct voltage and power. Although residual Al from soda cans was utilized, the results showed that the SAMFC stack delivered a maximum 3.77 V (I = 0 A) and 2.70 W of maximum power, which is only 18% lower than the same AMFC stack fed with pure H2 . In parallel, a simplified SAMFC stack transient mathematical model numerical results were validated by direct comparison to experimental data. A parametric analysis investigated the impact of electrolyte KOH mass fraction variation (y = 20%, y = 40%, and y = 50%) on performance, showing that there was an optimal condition, yopt = 40% w/w, for maximum SAMFC net power output, which was the adopted value in this work's experiments. Remarkable is that the maximum is sharp, since the net power drops by ∼42% with y = 50% w/w, and by 50% with y = 20% w/w in comparison to y = 40% w/w. It is concluded that in situ sustainable H2 generation coupled with the fuel cell stack showed potential to be a viable sustainable power generation system in the near future, mainly if operating at the herein found optimal operating conditions. Highlights: A sustainable alkaline membrane fuel cell stack is built and characterized. H2 is produced in situ from commercial and residual Al from soda cans. The SAMFC stack power was 18% lower than the AMFC stack with pure H2 . The model was validated with good quantitative and qualitative agreement. The SAMFC stack demonstrated potential for sustainable power generation.